The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Advances in Polymer Science
DOI: 10.1007/bfb0025902
|View full text |Cite
|
Sign up to set email alerts
|

Network formation by chain crosslinking photopolymerization and its applications in electronics

Abstract: The formation of densely crosslinked networks by chain crosslinking photopolymerization is discussed in relation to selected applications in the electronics industry. All of these applications make use of the high speed and of the latitude to meet other requirements by variation of the chemical structure of the monomers. The selection comprises: 1. The coating of optical fibers ; 2. The replication of optical discs; 3. The replication of aspherical lenses, used for laser read-out of these discs. Other importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
202
0
4

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(213 citation statements)
references
References 137 publications
7
202
0
4
Order By: Relevance
“…A third stage in which polymerization continues at very low rate, attributed to vitrification [35] was not present, in agreement with the fact that the T g of the polymers used in this study is lower than the polymerization temperature. However for PFOA based materials the reaction rate versus conversion curve shows a shoulder at a conversion of about 0.8 (Fig.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…A third stage in which polymerization continues at very low rate, attributed to vitrification [35] was not present, in agreement with the fact that the T g of the polymers used in this study is lower than the polymerization temperature. However for PFOA based materials the reaction rate versus conversion curve shows a shoulder at a conversion of about 0.8 (Fig.…”
supporting
confidence: 89%
“…the product of the time of the exposure and the light intensity [33,34]. On the other hand some researchers found that the final conversion and properties of the polymerized materials depended on the light intensity [17,21,35,36]. The contradictory results obtained brought up the debate on the applicability to the photopolymerization of acrylates of the radiant exposure reciprocity law, stating that it is only the energy dose that determines the final effect on the light sensitive material [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In photoinitiated free-radical polymerization 13 , carbon-based radicals derived from organic initiator molecules react with the carbon-carbon double bonds of acrylate monomers, and polymers are formed via a chain-growth mechanism. The concept of amplification is inherent in chain-growth polymerization reactions owing to the extremely large number of propagation steps that result from a single initiation event.…”
mentioning
confidence: 99%
“…Because of good thermomechanical properties, crosslinked (meth)acrylates have found use in a wide variety of applications. They are successfully employed in coatings for flooring and furniture, dental restorative materials, optical fibers, hard and soft contact lenses, and photolithography [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%